2019
DOI: 10.29407/jmen.v5i2.12814
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan model pembelajaran group investigation pada materi lingkaran untuk meningkatkan kemampuan berpikir kritis

Abstract: Masalah yang melatarbelakangi penelitian ini, peserta didik mengalami kesulitan dalam menyelesaikan soal High Order Thinking Skill (HOTS) terkait materi lingkaran, ini terjadi karena rata-rata kemampuan berpikir kritis peserta didik tergolong rendah sampai sedang. Salah satu alternatif meningkatkan kemampuan berpikir kritis adalah menerapkan model pembelajaran Group Investigation. Penelitian ini bertujuan meningkatkan kemampuan berpikir kritis dalam memahami materi lingkaran melalui metode pembelajaran Group I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
3
0
3
Order By: Relevance
“…This is also in line with opinion (Ariawan, 2016) that the group investigation type cooperative model made students active in constructing their knowledge, able to structure and solve problems through critical, creative, analytical, and productive thinking. This is supported by the findings (Lestari, 2019) which showed that through the group investigation model students were allowed to be scientific by developing curiosity, honesty, openness, diligence, and thoroughness. The group investigation learning model provided an opportunity for students to determine their problems and required students to find solutions through systematic steps so that through this process students were trained in using critical thinking skills.…”
Section: Findings and Discussionsupporting
confidence: 53%
“…This is also in line with opinion (Ariawan, 2016) that the group investigation type cooperative model made students active in constructing their knowledge, able to structure and solve problems through critical, creative, analytical, and productive thinking. This is supported by the findings (Lestari, 2019) which showed that through the group investigation model students were allowed to be scientific by developing curiosity, honesty, openness, diligence, and thoroughness. The group investigation learning model provided an opportunity for students to determine their problems and required students to find solutions through systematic steps so that through this process students were trained in using critical thinking skills.…”
Section: Findings and Discussionsupporting
confidence: 53%
“…It can be concluded that the results of student learning through the implementation of a group investigation learning model through mathematical domino media better than the implementation of a conventional learning model on the rank number and root form materials in grade IX of SMP Negeri 1 Lhokseumawe. This is by previous research (Haridi, 2018) which concluded that there was an improvement in the results of learning mathematics through group investigative learning models and previous research (Lestari et al, 2019) which concluded that the implementation of group investigation learning models can improve the critical thinking skills of class XI students in circle materials.…”
Section: ▪ the Initial Variance Homogeneity Testmentioning
confidence: 59%
“…(1,658 <1,965). Whereas, [36] reported the results of the study showed that the Investigation learning method could improve students' critical thinking skills by 25.44%. On the other hand, [37] states that there is a group investigation effect on students' conceptual understanding.…”
Section: Discussionmentioning
confidence: 99%